Quality of urban public transport websites according to extent of provided information - Bulíček, Josef; Drdla, Pavel (Transport, 2015)
This paper is based on the analysis of websites of Urban Public Transport (UPT) made in different states. The paper proposes a standard of ‘minimal information websites content’ named as ‘Passenger Friendly Web’. Information content is divided into a set of elements. Their weights are determined by expert evaluation with the support of mathematics, especially of Saaty’s Method. Possibilities for future research are also regarded. Results can be applied to all Internet websites of UPT.